Programa de estimulação psicomotora aquática para crianças com deficiência visual com a participação das mães - Storch, Jalusa Andréia (2013)
The aquatic psychomotor is one of the approaches to psychomotor, which uses water as a means of action more global and can be considered an effective approach to aid in motor development of children with visual impairment. Thus, this study aimed to develop and implement a program of Psychomotor Stimulation Aquatic (PEPA) for children with visual disabilities by participating mothers. The methodology selected for this study was based on descriptive and cross-sectional design outlined by the evaluative case study. Participants were selected for sampling based on criteria consisting of six participants, three visually impaired children - blind, low vision, of both genders, with two to three years of age, respectively accompanied by their mothers (n = 05 ), which were analyzed pre-and post-testing, applying intervention. The instruments used for data collection were: Screenplay by Anamnesis; Motor Functional Evaluation, and Field Diary. Data were analyzed qualitatively by analytical narrative and analysis of content. The intervention trasncorreu in two different cities, located in the western state of Paraná, in the premises of thermal pools heated. The program consisted of two phases, the first - enabling mothers in the liquid medium and the materials used, and the second step - the application of aquatic psychomotor stimulation in children with visual impairment. The program consists of 26 lessons was applied to each dyad separately, the frequency of twice a week, lasting 30 minutes to an hour / class. The activities were planned in advance by the researcher, based on the assessments of participants by means of the data collection. The results revealed that the PEPA program promoted positive increments on the motor development of all participating children, regarding the acquisition of postural reactions (reactions protective posture in sitting and standing) in the visual and motor skills (manipulation of objects, search objects and increments following objects in the seated position), plus acquisitions in posture and motor skills (acquisition movements and postural control in sitting and standing). Finally, it was found that the methodological option of joint participation of the dyad in the liquid medium, allowed an exchange of experience between researcher and participants, and have promoted mutual learning between mother and child (a), whose learning was transferred to the home environment and social context in which children with visual impairment are inserted.